Arbuscular mycorrhizal fungi alleviates salt stress in Xanthoceras sorbifolium through improved osmotic tolerance, antioxidant activity, and photosynthesis - Zong, Jianwei; Zhang, Zhilong; Huang, Peilu; Yang, Yuhua (Frontiers in Microbiology, 2023)
Mycorrhizal inoculation was widely reported to alleviate the damage resulting from NaCl by various physiological ways. However, the symbiotic benefit under distant NaCl concentrations and the relationship among different responsive physiological processes were elusive. In this study, saline resistant plant Xanthoceras sorbifolium was selected as the experimental material and five concentrations of NaCl in the presence or absence of AMF (Arbuscular Mycorrhiza Fungi) were conducted, in order to understand the differences and similarities on the photosynthesis, antioxidant activity and osmotic adjustment between arbuscular mycorrhizal (AM) plants and non-arbuscular mycorrhizal (NM) plants. Under low salt stress, X. sorbifolium can adapt to salinity by accumulating osmotic adjustment substances such as soluble protein and proline, increasing superoxide dismutase (SOD), catalase (CAT) activity and glutathione (GSH). However, under high concentrations of NaCl (240 and 320 mM(mmol·L-1)), the resistant ability of the plants significantly decreased, as evidenced by the significant downregulation of photosynthetic capacity and biomass compared with the control plants in both AM and NM groups. This demonstrates that the regulatory capacity of X. sorbifolium was limiting, and it played a crucial role mainly under the conditions of 0-160 mM NaCl. After inoculation of AMF, the concentration of Na+ in roots was apparently lower than that of NM plants, whilst Gs (Stomatal conductance) and Ci (Intercellular CO2 concentration) increased, leading to increases in Pn (Net photosynthetic rate) as well. Moreover, under high salt stress, proline, soluble protein, GSH and reduced ascorbic acid (ASA) in AM plants are higher in comparison with NM plants, revealing that mycorrhizal symbiotic benefits are more crucial against severe salinity toxicity. Meanwhile, X. sorbifolium itself has relatively high tolerance to salinity, and AMF inoculation can significantly increase the resistant ability against NaCl, whose function was more important under high concentrations.